Campaigns to Capture Young Minds: A Look at Early Attempts in Colonial Mexico and New France to Remold Amerindians - Dickason, Olive (Historical Papers / Communications historiques)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 1987)
AbstractBoth French and Spanish authorities saw the education of Amerindians as an essential tool in assimilating them to European ways. Both groups thought that the natives were either uneducated, and therefore clean slates for new teachings, or else sufficiently capable of understanding the superiority of foreign ways. In either case, education was the necessary vehicle for turning the natives towards European habits and norms of behaviour. The approach of each group was different. The Spanish, through the Franciscans, were able to take over an existing system, altering it to suit their own needs. They therefore devised a sophisticated system of institutions quickly, establishing a college by 1536. These efforts enjoyed a huge initial success, largely because the natives in their defeat experienced little difficulty in substituting one set of authority figures for another set already found wanting. The French were not conquerers, and did not face a native society in crisis, as had the Spanish. The French Franciscan friars also initiated christianizing education quickly after first settlement, but the Jesuits superceded them within two decades. The natives agreed to their ministrations because the French made it a condition of trade. Huron society differed radically from that of the Mexico, in its egalitarian structure and flexible institutions. The Huron, an unconquered people in a transitional phase of social and economic life, treated the missionaries as guests and often dictated the conditions of contact. In spite of quite different circumstances, the educational efforts of both groups seem to have reached a similar conclusion: native groups were neither as maleable nor as easy to assimilate as the Europeans had thought.